Perception of digital reading material for academic purposes among UMK undergraduates / Noor Syamimie Mohd Nawi ... [et al.] - Mohd Nawi, Noor Syamimie; Ramamurthy, Lena; Shafien, Syakirah; Omar, Suhaida; Nik Azim, Nik Ahmad Farhan (2021)
The inclusion of technology in language learning is a new norm particularly when almost everyone, including students, is using electronic gadgets (connected to internet) such as smartphones, tablets and computer in their daily life, especially now. The aim of this project is to identify the students’ perceptions on their usage of electronic gadgets in relation to academic reading and writing since they spend a lot of time browsing and reading digital reading material (DRM) online or offline. Throughout the project, we are trying to digitalize reading and writing component in ESL classroom in UMK by changing them from conventional reading and writing. Thus, we are piloting it through English for Business Communication course. For this specific project, a module is developed and it focuses on first semester undergraduates from Business Faculty in Universiti Malaysia Kelantan. Respondents have been using the module for the past 14 weeks (1 semester) and their responses were recorded using qualitative method through online questionnaires and interviews. The teachers considered digitalized reading materials suit the students’ needs and the course syllabus. The findings revealed that more than half the undergraduates would prefer to use digital reading material for academic purposes. Lastly, this project serves as a basis for the educators to provide suitable online reading material in helping students for their academic reading and writing purposes.